Relasi Antara Budaya Sasak dan Islam: Kajian Berdasarkan Perspektif Folklor Lisan Sasak - Fakihuddin, Lalu (Universitas Hamzanwadi, 2018)
The purpuse of the research is uncovering a through a link between Sasak culture and islamic of perspective Sasak folklore. In addition, reseach in also intended to increase appreciation sasak society, especially academic society. Design used in this research is descriptive-qualitative. This design was chosen becaouse relevance with a gool and data the nature of researcch, that is: (1) the use of documents of a literary work, namely the text of folklore and hikayat as an object of the study, (2) the data of this study in tehe form of writing, in the form of sequences interlocking of the text of myth, folklore, and hikayat the relationship between sasak culture and values of islam, (3) the focus of the research as of as values, and (4) the research process is based on the interpretative. In this kind of methodology research and analyzed with the hermeneutc , wich is to interpret a texs... so they can understand a lot of people at the dipperent priod. Data in the study are collected by a documentation. The key instrument to this research is a researcher. The result of the research, namely Sasak culture, especially the folklore, possesses remarkably subtle hints of islam, the fact presented indicated that the teachins of islam through Sasak culture (through myte, folklore, and hikayat), it is also a intrnalisasion the teaching of islam or islamis values. It is of course not limited to the problems that has been presented, but also appear in a form of Sasak cultures, like rudat and and nyair tradistions.Keywords: relasion; Sasak culture; Islam; oral folklor.